QUANTITATIVE DETECTION OF MICRORNA-20A AMONG IRAQI COLORECTAL CANCER PATIENTS - Hiba A. Mohammed; Nuha J. Kandala; Noor Saber (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study aimed to investigate the expression level of microRNA-20a in plasma samples collected from 20 healthy males and 20 healthy females’ as non-cancerous controls, 34 males and 26 females who diagnosed with CRC, the age range for both poles was at age range of 23 to 66 years old, those patients didn’t receive any chemical, radiological or surgical treatment and subjected to relative quantitative detection using RT-PCR technique. Specific primers designed for this purpose, the sequence of miR-20a retrieved from NCBI and miRBASE, the primers designed using stem-loop structure method, RNU-43 reference gene used for results normalization. The resulted data analyzed using the Livak method, the folding mean of CRC patients (12.78) was higher than the folding level of non-cancerous controls (1.6909), 28 patients were had higher folding levels than the mean of the controls while 32 patients were below the non-cancerous controls folding mean. Among 60 patients, 22 samples were had expression levels less than 1 folding level, 11 samples had expression levels less than 2 folding levels, 12 samples quantified folding less than 5 folding levels, 8 samples were less than 20 folding levels, and 7 samples with higher 20 folding level, such results indicated that the expression level of microRNA-20a is changed and dose not remain consistent in colorectal cancer patients, with varied quantified results due to different factors. No considerable statistical relevance to age and gender was revealed since P values were greater than 0.05 level in Students-t-test and ANOVA test.